Synthesis and properties of na nomagnetite for the preparation of biocomposites - Synytsia, A.O.; Iatsenko, A.P.; Sych, O. Ye.; Babutina, T.Ye.; Тоmila, T.V.; Bykov, O.I.; Perekos, A.O.; Boshytska, N.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
Magnetite powder (FeO·Fe2O3 or Fe3O4) is obtained by the chemical precipitation method, using FeCl3·6H2O and FeCl2·4H2O as a starting materials in the presence of hydrazine N2H4 at a temperature of 80 °C. X-ray diffraction analysis, infrared spectroscopy, and scanning electron microscopy are used for the study of the phase composition and morphology of the synthesized powder. Its specific surface area and magnetic properties such as, in particular, the specific saturation magnetization, coercive force and residual induction are investigated. It is established that the composition of the synthesized powder is represented by magnetite as the main phase with a small admixture of hematite. It is shown that the particles of the obtained magnetite have sizes of 33-84 nm and tend to the agglomeration. The prepared powder has superparamagnetic properties (specific magnetization — 35 A · m2/kg, coercive force — 0.24 kA/m, residual induction — 0.009 T) and is promising for the biocomposite creation.